Distribución, densidad y estructura de talla de Oreaster reticulatus y Luidia senegalensis (Echinodermata: Asteroidea) en isla de Cubagua, Venezuela Distribution, density an size structure of Oreaster reticulatus and Luidia senegalensis (Echinodermata: Asteroidea) in Cubagua Island, Venezuela - Alejandro Tagliafico; María Salomé Rangel; Néstor Rago (Revista de Biología Tropical, 2012)
Las estrellas de mar: Oreaster reticulatus y Luidia senegalensis, han sido objeto de escasos estudios en aguas venezolanas. Actualmente son consideradas especies amenazadas en diversas zonas del Caribe, Brasil y Colombia. Por esto, se planteó como objetivo generar información sobre su densidad poblacional, distribución y estructura de talla en los alrededores de la isla de Cubagua. Para ello, durante el año 2008, se realizaron cuatro transectas bandas de 50m2 cada una, en 52 estaciones ubicadas alrededor de la isla. Entre los resultados obtenidos para O. reticulatus destacan: 167.3ind/ha, un 33% inmaduros y 67% adultos con un promedio de tallas de 10.7±5cm (rango: 2.2-21cm); una amplia distribución en los alrededores de la isla, con mayores densidades en la zona este y suroeste. Luidia senegalensis mostró una densidad promedio de 40ind/ha, 95% superaba la talla de madurez reportada, con talla promedio de 12cm±3.5cm (rango: 3.5-22.3cm). Se recomienda realizar estudios de reproducción, así como monitoreos de sus densidades poblacionales que permitan inferir sus variaciones temporales. There is limited biological information about the starfish Oreaster reticulatus and the nine-armed starfish Luidia senegalensis in Venezuelan waters. These species are currently considered threatened in many localities of the Caribbean, Brazil and Colombia. Therefore, the aim of this study was to describe their population density, size distribution and population structure in Cubagua Island. During 2008, 52 stations located around the island were evaluated using band transects of 50m2. Each organism was counted and measured (maximum radius), and its size was compared to the maturity length reported in the literature. The results for O. reticulatus include: 167.3ind./ha; 33% juveniles and 67% adults; average size of 10.7±5cm (range: 2.2-21cm); a wide distribution around the island, with higher densities in the Eastern and Southwest areas. The 50% of the specimens were found in seagrass beds, 25% in sand, 16% in areas covered by decomposed seaweeds, 9% in oyster beds and 1% coralline patches. The densities of O. reticulatus were higher than those reported in the Caribbean, Panama and Puerto Rico, but lower than Venezuelan National Parks: Mochima and Morrocoy; as well as in the Virgin Islands and Belize. For L. senegalensis we found an average density of 40ind./ha; 95% exceeded the reported size at maturity, with mean length of 12cm±3.5cm (range: 3.5-22.3cm); they were found only in 15% of the stations of which 92.5% were sandy bottoms and the other 7.5% oyster beds. The degree of aggregation of L. senegalensis was greater than O. reticulatus, with an estimated k of 0.06. However, it was not possible to compare the densities of L. senegalensis with any other study. For both species is recommended to carry out reproductive studies and to monitor their population densities to infer temporal variations.